Distinct positive temperature coefficient effect of polymer–carbon fiber composites evaluated in terms of polymer absorption on fiber surface. Issue 11 (29th February 2016) - Zhang, Xi; Zheng, Shaodi; Zheng, Xiaofang; Liu, Zhengying; Yang, Wei; Yang, Mingbo
Abstract : The positive temperature coefficient (PTC) effect for high-density polyethylene (HDPE)/carbon fiber (CF) composites was studied. Abstract : In this article, the positive temperature coefficient (PTC) effect was studied for high-density polyethylene (HDPE)/carbon fiber (CF) composites. All of the samples showed a significant PTC effect during the heating processes without a negative temperature coefficient (NTC) effect, even at a temperature much higher than the melting point of the polymer matrix. An ever-increasing PTC intensity with increasing thermal cycles was observed in our study that had never been reported in previous research. The absence of a NTC effect resulted from the increased binding force between the matrix and fillers that contributed to the very special structure of CF surface. We incorporated thermal expansion theory and quantum tunneling effects to explain PTC effect. From the SEM micrographs for the HDPE/CF composites before and after the different thermal cycles, we found that the surface of CF was covered with a layer of polymer which resulted in a change in the gap length between CF and HDPE and its distribution. We believed that the gap change induced by polymer absorption on the fiber surface had a great effect on the PTC effect.